Training Head Start Teachers to Conduct Trial-Based Functional Analysis of Challenging Behavior. (October 2015) - Rispoli, Mandy; Burke, Mack D.; Hatton, Heather; Ninci, Jennifer; Zaini, Samar; Sanchez, Lisa
Trial-based functional analysis (TBFA) is a procedure for experimentally identifying the function of challenging behavior within applied settings. The purpose of this study was to examine the effects of a TBFA teacher-training package in the context of two Head Start centers implementing programwide positive behavior support (PWPBS). Four Head Start teachers were trained in TBFA procedures as part of ongoing technical assistance on individualized behavior supports. Following training and performance feedback, all teachers were able to implement TBFA with 100% fidelity during simulation probes. With minimal additional coaching, teachers implemented TBFA sessions with a child in their classroom with 100% fidelity. Implications for future research and for the use of TBFA in early childhood settings are presented.